2021
DOI: 10.1186/s42834-021-00110-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic performance of Nb doped TiO2/reduced graphene oxide nanocomposites over rhodamine B dye under visible light illumination

Abstract: The present study discusses the synthesis of Nb doped TiO2/reduced graphene oxide (rGO) intercalated nanocomposites via sol-gel route at a lower temperature by using different loading amounts of graphene oxide (GO) (1 to 10 wt%). The synthesized composite materials were further characterized by copious instruments such as X-ray Diffractometer, UV-Vis Diffuse Reflectance Spectroscopy, Scanning Electron Microscopy, Transmission Electron Microscopy, Brunauer-Emmett-Teller surface area analysis, Raman and Fourier … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As shown in Supplementary Table S2, it was found that among all materials, Z-PAgT-5 displayed the highest degradation efficiency with 0.067 mg/g/min, indicating its high photocatalytic removal ability for Rh B. As for Zeolite/g-C 3 N 4 (Kumar et al, 2018), CdS/ TiO 2 (Wang et al, 2019), SiO 2 /CNOs/TiO 2 (3%) (Zhang et al, 2019), g-C 3 N 4 /Ag-TiO 2 (2%) (Sui et al, 2020), and Nb-doped TiO 2 /rGO (Prabhakarrao et al, 2021), their photocatalytic efficiency was dramatically lower than Z-PAgT-5. As such, all the abovestated results suggest that our created Z-PAgT-5 photocatalyst with high photocatalytic efficiency and stability for numerous cycles is a promising alternative for wastewater treatment in practical applications.…”
Section: Stability Of the Prepared 3dzeolite-modified Photocatalystmentioning
confidence: 99%
“…As shown in Supplementary Table S2, it was found that among all materials, Z-PAgT-5 displayed the highest degradation efficiency with 0.067 mg/g/min, indicating its high photocatalytic removal ability for Rh B. As for Zeolite/g-C 3 N 4 (Kumar et al, 2018), CdS/ TiO 2 (Wang et al, 2019), SiO 2 /CNOs/TiO 2 (3%) (Zhang et al, 2019), g-C 3 N 4 /Ag-TiO 2 (2%) (Sui et al, 2020), and Nb-doped TiO 2 /rGO (Prabhakarrao et al, 2021), their photocatalytic efficiency was dramatically lower than Z-PAgT-5. As such, all the abovestated results suggest that our created Z-PAgT-5 photocatalyst with high photocatalytic efficiency and stability for numerous cycles is a promising alternative for wastewater treatment in practical applications.…”
Section: Stability Of the Prepared 3dzeolite-modified Photocatalystmentioning
confidence: 99%
“…Graphene-based nanocomposites have attracted attention for a variety of applications, including gas sensing, energy storage, environmental remediation, and biomedicine. , Presently, several investigators are focusing on fabricating metal oxide nanocomposites (NCs) with GO or rGO nanosheets to improve their optical properties . Jo et al reported that the incorporation of graphitic carbon with TiO 2 NPs enhanced their photocatalytic activity under UV irradiation compared with pure TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Presently, several investigators are focusing on fabricating metal oxide nanocomposites (NCs) with GO or rGO nanosheets to improve their optical properties. 24 Jo et al 25 reported that the incorporation of graphitic carbon with TiO 2 NPs enhanced their photocatalytic activity under UV irradiation compared with pure TiO 2 NPs. The TiO 2 /WO 3 /GO NCs demonstrate outstanding photocatalytic activity for the degradation of bisphenol under visible light.…”
Section: Introductionmentioning
confidence: 99%